AKTIVITAS PENGASUHAN ANAK PADA IBU USIA REMAJA - Irene Puspita; Yapina Widyawati (MANASA, 2013)
Parenting is any action taken by adults to children in order to fulfill their needs. The role of parents usually experienced when a person is in the young adult stage,in the age range 20 to 30 years. Today, being a parent can also happen in adolescence. The number of adolescence who eventually becomes parent has increased. It can be caused by many things. Children born from adolescence mothers could experience some of the risk in terms of physical and cognitive. In this condition the parenting role still should be taken.The objective of this research wasto have better description on parenting activities carried out by mother to her children. It used qualitative research method based on the theory of parenting by Hoghughi. Subjects in this study were four adolesence mothers who had childfrom pre-marital sexual relations. The result of the study explained that children growing up according to developmental milestone and get enough parenting care. The parenting activities consist of parenting attention, control, and development. Adolescence mother are also able to meet childneeds and make their own decisions as they do in the young adult stage of development. Social supports have influence the mother parenting activity.